2019
DOI: 10.1016/j.compgeo.2019.103154
|View full text |Cite
|
Sign up to set email alerts
|

Discrete element modelling of flexible membrane boundaries for triaxial tests

Abstract: The discrete element modelling (DEM) of triaxial tests plays a critical role in 2 unveiling fundamental properties of particulate materials, but the numerical 3 implementation of a flexible membrane boundary for the testing still imposes 4 problems. In this study, a robust algorithm was proposed to reproduce a flexible 5 membrane boundary in triaxial testing. The equivalence of strain energy enables the 6 particle-scale parameters representing the flexible membrane to be directly 7 determined from the real geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 78 publications
0
40
0
Order By: Relevance
“…Shear localization is a remarkable sign of the instability of ductile solid materials, such as granular materials. When the material deforms sufficiently into the plastic state, a homogeneous deformation pattern gives way to highly localized deformation featured as a “shear band.” 38 It mainly occurs in dense granular materials under large deformations. The conventional RVE model with homogeneous deformation assumption is unable to reasonably reflect such a strain localization phenomenon at the RVE level.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…Shear localization is a remarkable sign of the instability of ductile solid materials, such as granular materials. When the material deforms sufficiently into the plastic state, a homogeneous deformation pattern gives way to highly localized deformation featured as a “shear band.” 38 It mainly occurs in dense granular materials under large deformations. The conventional RVE model with homogeneous deformation assumption is unable to reasonably reflect such a strain localization phenomenon at the RVE level.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…The conventional triaxial test is one of the standardized laboratory tests, which plays a fundamental role in geotechnical engineering researches 1 . By using the equipment, the stress–strain curve of a rock block under special confining pressure can be obtained, so as to investigate the deformation and failure process of the rock under complicated conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have confirmed the ability of discrete element modelling (DEM) to capture intrinsic features of granular materials . However, the choices of DEM parameters are often made in a trial and error manner . A barrier to determining reasonable contact parameters is that a direct measure of particle‐scale parameters is difficult for granular systems with several different constituents.…”
Section: Introductionmentioning
confidence: 99%